2017
DOI: 10.18203/2349-3291.ijcp20171526
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin D levels and transient tachypnea of newborn: a case control study

Abstract: Background: Transient tachypnea of newborn (TTN) is a common cause of respiratory distress in newborns with estimated incidence of 1-2% of all newborns. Although a self-limiting transient condition but it may cause severe morbidities. This study was conducted to find association of serum vitamin D levels in neonates who develop TTN as compared to normal healthy neonates.Methods: With thorough history with structured questionnaire and lab tests, serum vitamin D levels of 45 neonates who develop TTN were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
0
0
3
Order By: Relevance
“…In neonates, forms of the vitamin taken orally reach equivalence in their capacity to increase circulation vitamin D levels at a postnatal age of about 89 days [38]. Preterm and term infants born with vitamin D deficiency are more likely to experience respiratory distress syndrome, neonatal transient tachypnea (TTN), acute lower respiratory tract infection, and early and late neonatal sepsis (LOS) than infants with optimal vitamin D levels, according to published research on the effects of vitamin D on the respiratory and immune systems [39][40][41][42][43]. As mentioned in the literature, our study also revealed that infants with low cord vitamin D levels had higher rates of respiratory distress from neonatal transient tachypnea and EOS, as well as longer hospital stays both in terms of frequency and duration.…”
Section: Discussionmentioning
confidence: 99%
“…In neonates, forms of the vitamin taken orally reach equivalence in their capacity to increase circulation vitamin D levels at a postnatal age of about 89 days [38]. Preterm and term infants born with vitamin D deficiency are more likely to experience respiratory distress syndrome, neonatal transient tachypnea (TTN), acute lower respiratory tract infection, and early and late neonatal sepsis (LOS) than infants with optimal vitamin D levels, according to published research on the effects of vitamin D on the respiratory and immune systems [39][40][41][42][43]. As mentioned in the literature, our study also revealed that infants with low cord vitamin D levels had higher rates of respiratory distress from neonatal transient tachypnea and EOS, as well as longer hospital stays both in terms of frequency and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Tedavi süresi uzamış YGT de sürfaktan yetersizliği veya disfonksiyonunun göz önünde bulundurulmasını gerektiğini savunan yazarlar da vardır (16,17) . Vitamin D eksikliği, akciğer yapısında değişiklikler ile birlikte sürfaktan üretiminde bozulmaya da neden olabilir (18) . Machado ve ark.…”
Section: Discussionunclassified
“…Yenidoğanlarda tüm solunum sıkıntısı nedenlerinin %40'ından fazlasını YGT oluştururken YGT dışı en sık görülen solunum sıkıntısı nedenlerini pnömoni, mekonyum aspirasyon sendromu, pnömotoraks, pulmoner arteryel hipertansiyon, hipoksik iskemik ensefolopati oluşturmaktadır (18) . Çalışmamızda, solunum Karatekin ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation